Wave energy resource assessment at southern coast of the Gulf of Mexico (2015)
Find alternative energy sources is one of the challenges that came with XXI century and this paper makes an analysis about wave energy, which presents several advantages over fossil based energy and even other renewable energy sources. Among them are its low environmental impact and its high energy density. Wave energy is beginning to be considered as an important and promising renewable resource in many countries. The objective of this paper is to evaluate the wave energy potential at the southern coast of the Gulf of Mexico; the sea states were observed and was obtained that the available mean wave power is 55.91 W/m. In addition, this paper shows that, in the study site, the most energetic season is fall and the less energetic season is spring. This differs from the global trend, were the most energetic season is winter, and the less energetic season is spring.